The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2ma00279e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical ammonia synthesis: fundamental practices and recent developments in transition metal boride, carbide and nitride-class of catalysts

Abstract: Ammonia, the value-added chemical, major fertilizer and future transportation fuel is conventionally and synthetically produced by the energy intensive Haber-Bosch process. For the conversion of nitrogen to ammonia, more energy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 185 publications
0
21
0
Order By: Relevance
“…Here, we critically assess the electrocatalytic NRR activity of molybdenum and iron carbides, where more than 10 independent literature reports claim to observe superior or excellent catalytic performance. 23 , 24 , 31 38 In the present work, α-Mo 2 C nanodots from Cheng et al (reported as the most promising carbide catalyst) are reproduced and compared with α-Mo 2 C nanoparticles as a benchmark. 23 Additionally, nanostructured θ-Fe 3 C and χ-Fe 5 C 2 are synthesized and examined for their NRR activity.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Here, we critically assess the electrocatalytic NRR activity of molybdenum and iron carbides, where more than 10 independent literature reports claim to observe superior or excellent catalytic performance. 23 , 24 , 31 38 In the present work, α-Mo 2 C nanodots from Cheng et al (reported as the most promising carbide catalyst) are reproduced and compared with α-Mo 2 C nanoparticles as a benchmark. 23 Additionally, nanostructured θ-Fe 3 C and χ-Fe 5 C 2 are synthesized and examined for their NRR activity.…”
Section: Introductionmentioning
confidence: 96%
“…As a consequence, a handful of research groups have tried to reproduce electrocatalysts initially labeled as promising, such as Fe, Bi, Au, VN, CoMo, Mo 2 N, and MoS 2 , ,, but discovered that the quantified ammonia must originate from sources other than the NRR. Here, we critically assess the electrocatalytic NRR activity of molybdenum and iron carbides, where more than 10 independent literature reports claim to observe superior or excellent catalytic performance. ,, In the present work, α-Mo 2 C nanodots from Cheng et al (reported as the most promising carbide catalyst) are reproduced and compared with α-Mo 2 C nanoparticles as a benchmark . Additionally, nanostructured θ-Fe 3 C and χ-Fe 5 C 2 are synthesized and examined for their NRR activity.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal borides, also known as MBenes, are an emergent class of catalysts that are still in their infancy in the electrochemical NRR eld. [187][188][189] MBenes as NRR electrocatalysts have the advantage of dual active edges from both the exposed metal end and the exposed boride end. 190 In the previous section, we have elaborated on how the electrons and orbitals of iron activate nitrogen bonds.…”
Section: Iron Boridementioning
confidence: 99%
“…Currently, extensive efforts have been contributed to design high-efficient NRR catalysts to achieve high-efficiency-NRR performance . To date, many metal-based catalysts have been designed theoretically or prepared experimentally, including noble-metals (Ru, Rh, Pt, Au, and Ag), transition metal sulfides (CoS 2 and MoS 2 ), nitrides (VN, Mo 2 N), phosphides (δ-AlP 3 ), carbides (Mo 2 C), and oxides (Mo-doped W 18 O 49 and Fe 2 O 3 –CNT).…”
Section: Introductionmentioning
confidence: 99%
“…17−19 Currently, extensive efforts have been contributed to design high-efficient NRR catalysts to achieve high-efficiency-NRR performance. 20 To date, many metal-based catalysts have been designed theoretically or prepared experimentally, including noble-metals (Ru, 21 Rh, 22 Pt, 23 Au, 24 and Ag 25 ), transition metal sulfides (CoS 2 26 and MoS 2 27 ), nitrides (VN, 28 Mo 2 N 29 ), phosphides (δ-AlP 3 30 ), carbides (Mo 2 C 31 ), and oxides (Modoped W 18 O 49 32 and Fe 2 O 3 −CNT 33 ). It is generally recognized that the coexistent occupied and empty d orbitals can back-donate π-electrons to and accept lone-pair electrons from N 2 , which determines the origin of the NRR activity for these transition metal (TM) containing catalysts.…”
Section: Introductionmentioning
confidence: 99%